Analisis Pelayanan Surat Izin Mengemudi Menggunakan Perspektif Dynamic Governance di Kantor Satuan Penyelenggara Administrasi Surat Izin Mengemudi Colombo Kota Surabaya - Solehuddin; Dida Rahmadanik; Adi Soesiantoro (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Online SIM service policy, Satpas Colombo Surabaya continues to strive to improve online SIM services so that urban residents of Surabaya who have very high mobility and are busy can still extend their SIM through online SIM which can be done at Satpas Colombo, Surabaya City. The government's commitment to improving public services in Indonesia through improving governance or reforming the bureaucracy to create good governance by referring to three indicators, namely Thinking Ahead, Thinking Again, and Thinking Across. This study aims to analyze the application of dynamic governance in the implementation of public services at the SATPAS Colombo Office, Surabaya City. This study uses a qualitative method that uses primary data and secondary data collected through observation, interviews, and documentation. The results of this study indicate that the Driving License (SIM) service at SATPAS Colombo Surabaya has shown significant progress through the application of the Dynamic Governance concept, especially with the use of information technology in the online SIM registration and management system which increases efficiency, transparency, and accessibility. This innovation is strengthened by routine evaluation, cross-sector collaboration, as well as proactive leadership support and employee readiness to face change. However, its implementation still faces a number of obstacles such as technical disruptions, limited ICT infrastructure in several areas, low digital literacy among the community, and minimal public involvement in the service planning and evaluation process.